Urinary diversion - approaches and consequences - Stein, Raimund; Hohenfellner, Markus; Pahernik, Sascha (Deutsches Ärzteblatt, 2012)
Background: Bladder cancer is not a rare disease: In 2010, there were more than 70 000 affected patients in the United States. Radical cystectomy for the treatment of muscle invasive bladder cancer necessitates urinary diversion. Methods: We present the current options for urinary diversion and their different indications on the basis of a selective search for pertinent literature in PubMed and our own clinical experience. Results: When bladder cancer is treated with curative intent, continence-preserving orthotopic urinary bladder replacement is preferred. For heterotopic urinary bladder replacement, a reservoir is fashioned from an ileal or ileocecal segment. Urine is diverted to the rectum by way of the sigmoid colon. When bladder cancer is treated with palliative intent, non-continence-preserving cutaneous urinary diversion is usually performed: The creation either of a renal-cutaneous fistula or a self-retaining ureteral stent is a purely palliative procedure. In these interventions, the resorptive surface of the bowel segment used can no longer play its original physiological role in the gastrointestinal tract, even though its absorptive and secretory functions are still intact. This has metabolic consequences, because the diverted urine here comes into contact with a large area of bowel epithelium. Early preventive treatment must be provided against potentially serious complications such as metabolic acidosis and loss of bone density. The resection of ileal segments can also lead to malabsorption. The risk of secondary malignancy is elevated after either continence-preserving anal urinary diversion (>2%) or bladder augmentation (>1%). Conclusion: There are four options for urinary diversion after cystectomy that can be performed when surgery is performed with either curative or palliative intent. There are also a number of purely palliative interventions.